Analisis Pengaruh Bonus Demografi, Pertumbuhan Penduduk, Pengangguran, Inflasi, dan Indeks Demokrasi Indonesia terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Ovilania, Ovilania; Junaidi, Junaidi; Etik, Umiyati; Siti, Khodijah; Nurhayani, Nurhayani (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
This study aims to find out and analyze the influence of demographic bonus, population growth, unemployment, inflation, and Indonesia's democracy index on economic growth in Jambi Province from 2009 to 2024. The analysis methods used in this study are descriptive analysis and quantitative analysis. The data used in this study are secondary data from 2009-2024 on a quarterly basis, obtained from the Central Statistics Agency. The analysis tool used is the Error Correction Model (ECM). The research results show that the ECT value has a significant effect, indicating that there is an influence between variables in reaching long-term equilibrium. In the short-term impact, the demographic bonus, unemployment rate, inflation, and Indonesia's democracy index variables do not have a significant effect on economic growth in Jambi Province, while population growth has a significant effect on economic growth in Jambi Province. Meanwhile, in the long-term impact, population growth, unemployment rate, and inflation have a significant effect on economic growth in Jambi Province, while the demographic bonus and Indonesia's democracy index variables do not have a significant effect on economic growth in Jambi Province.